THE INFLUENCE OF INTERCULTURAL COMMUNICATION WITH THE ATTITUDES OF SOCIAL SOLIDARITY STUDENTS IN STATE SENIOR HIGH SCHOOL - mei rindi; Irawan suntoro; Muhammad Mona Adha (FKIP Unila, 2012)
Research is intended to explain the influence of intercultural communication with the attitudes of social solidarity students in state senior high school 1 punduh pedada pesawaran. Methods used in this research is a method of descriptive correlational. Population in this research is a senior high school student 1 punduh pedada pesawaran academic year 2012 / 2013 with a sample of 49 of respondents. Data in this research are collected through poll, and engineering data analysis using formulas correlation product moment. The result showed that there are the influence of intercultural communication with the attitudes of social solidarity students in state senior high school 1 punduh pedada pesawaran academic year 2012 / 2013. The influence of intercultural communication with the attitudes of social solidarity of students in the school is located in the prologue and strong. This would mean more effective intercultural communication attitudes social solidarity will produce students who high. On the contrary, less and less effective intercultural communication happens to be produce an attitudes of social solidarity students who low.Keywords: Intercultural Communication, attitude, social solidarity